A Rights-Based Preventative Approach for Psychosocial Well-Being in Childhood - Desai, Murli. (Children<U+00bf>s Well-Being: Indicators and Research, 2010)
Childhood is the most important stage of human development, a fact that makes children the central target group for social work intervention. In turn, most schools of human development and social work around the world have an elective course on children, with some offering a concentration in this area. Yet while there are plenty of textbooks on intervention with children that contain useful theories and skills, many focus on remedial rather than preventative strategies, and do not adopt a child rights perspective. In turn, books on child rights fail to link the latter either with theoretical background or the preventative approach. This book, aimed at faculty members and students in social work and related programs, breaks new ground by being the first to apply the child rights perspective and the preventative approach to intervention for children's psychosocial well-being. It covers crucial ground in child psychology, even providing an ecological perspective to potential developmental problems. Relevant to situations across the world, and integrating theory, practice and teaching, its three sections introduce the rights-based perspective to preventative intervention, then move on to examine primary, secondary and tertiary prevention for children<U+0019>s psychosocial well-being.